Sequences Similar to the lan-Cluster (Streptomyces cyanogenus S136) Were Found in the Genomes of Other Streptomycetes - Polishchuk, L.V.; Lukyanchuk, V.V.; Поліщук, Л.В.; Лук’янчук, В.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The aim of the work is to identify strains of streptomycetes in the genomes of which there are nucleotide sequences similar to the gene cluster determining the synthesis of landomycin A (lan-cluster) and establish the level of similarity of their primary structures and organizations. Methods. Information on the sequences of the lan-cluster of Streptomyces cyanogenus S136 and chromosomal DNAs of S. cyanogenus S136, Streptomyces laculatispora NRRL B-24909, and Streptomyces griseoluteus JCM 4765 and their annotations are presented in the GenBank database on the NSBI server. A computerized analysis of the nucleotide sequences of streptomycetes was done using the program BLASTN from the server NSBI. Results. The localization of the lan-cluster in the terminal region of the S. cyanogenus S136 genome has been shown. The nucleotide sequences similar to the lan-cluster sequence of S. cyanogenus S136 were found in the genomes of two strains (S. laculatispora NRRL B-24909 and S. griseoluteus JCM 4765). Streptomycetes (S. cyanogenus S136, S. laculatispora NRRL B-24909, and S. griseoluteus JCM 4765) are not genetically related strains. Conclusions. There are newly found probable lan-clusters in the genomes of two streptomycetes strains (S. laculatispora NRRL B-24909 and S. griseoluteus JCM 4765). Landomycin clusters of three strains are organized according to the same scheme. The clusters of lan-genes are present in the genomes of genetically unrelated streptomycetes.